4-3(5*0)+2=

Simple and best practice solution for 4-3(5*0)+2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-3(5*0)+2= equation:


Simplifying
4 + -3(5 * 0) + 2 = 0

Multiply 5 * 0
4 + -3(0) + 2 = 0

Anything times zero is zero.
4 + -3(0) + 2 = 0

Multiply -3 * 0
4 + 0 + 2 = 0

Anything times zero is zero.
4 + 0 + 2 = 0

Combine like terms: 4 + 0 = 4
4 + 2 = 0

Combine like terms: 4 + 2 = 6
6 = 0

Solving
6 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 10x-7+3x=5x+7-8x | | 4x-4=6x+7 | | 5/2x-7=3/4x+14 | | 2+2f=4 | | 5/4x-2=3/2x-4 | | x^2-64=60 | | 5/4x-9=3/2x-12 | | 32y-44= | | (-b-5x-3)+(2b-4x+7)= | | 5/2x+7/2=3/4x+14 | | 7.5c-2.5c+8=-7 | | m=6x | | 4.6y-y+4=y-1.2 | | 5m+3=4m+5 | | PFcmN44a2qyyu®a-//A©aecu6 | | 3.2b-4.7=3b-3.3 | | 1/4x+5/3x-4=2-1/12x | | 8x+-4=12 | | 4(x+10)=19 | | i^3= | | y-1(3+66)+12=1203 | | x-2*x*sqrt(z)+5*z=1 | | 3(x-5)-3x^2=-30 | | y-1(3-66)+12=1203 | | 8(2x+3)=48 | | 3(x+5)-3x^2=-30 | | 3y-7=2y+6 | | 8x-5+64=180 | | (1-2x)(1+2x)=0 | | ln(x)+(x-6)=ln(6x) | | -1/2+3/5= | | 7/10+7/10= |

Equations solver categories